2018
DOI: 10.1002/htj.21387
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of mixed convection nanofluid in an annulus enclosure between outer rotating cylinder and inner corrugation cylinder

Abstract: Numerical investigations are presented for mixed convection problems in a concentric inner sinusoidal cylinder and an outer rotating circular cylinder, which were kept at constant hot and cold temperatures, respectively. The free space between the cylinders and the enclosure walls was filled with a water‐Cu nanofluid. The governing equations are formulated for velocity, pressure, and temperature formulation and are modeled in COMSOL5.2a, a partial differential equation solver based on the Galerkin finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
(107 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, Hatami et al 23 26 applied the optimization techniques to improve the geometries and enhance the nanofluid heat- transfer in applications such as solar collectors. Farooq et al 27 studied Cu-water nanofluid flow in an annulus enclosure with inner rotating corrugation cylinder of an average Nusselt number can be improved by increasing the Rayleigh number. Also, Alsabery et al 28 studied Al 2 O 3 -water nanofluid in double lid-driven square cavity using two-phase method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hatami et al 23 26 applied the optimization techniques to improve the geometries and enhance the nanofluid heat- transfer in applications such as solar collectors. Farooq et al 27 studied Cu-water nanofluid flow in an annulus enclosure with inner rotating corrugation cylinder of an average Nusselt number can be improved by increasing the Rayleigh number. Also, Alsabery et al 28 studied Al 2 O 3 -water nanofluid in double lid-driven square cavity using two-phase method.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical analysis of the mixed convection in a square enclosure that contained a rotating circular cylinder with non-concentric positions was performed by Ali et al 43 They deduced that the best position for the rotating cylinder was at the left bottom corner of the enclosure. Ali et al 44 numerically studied the mixed convection of a nanofluid bounded by outer rotating and inner corrugated cylinders. Their results showed that there was a decrease in the average Nusselt number with an increase in the corrugation and the Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Natural heat transfer has gained importance in the last three decades for its various applications, such as cooling electronic devices and reducing energy leakage from energy conservation storages [1][2][3][4]. Aydin et al [5] used the stream function-vorticity formulation to study the effect of aspect ratio within rectangular enclosures.…”
Section: Introductionmentioning
confidence: 99%